The Influence Of E-Wallet Use on Consumptive Behavior of Mataram City Communities Moderate by Self-Control - Karthika, Nyoman Suryadina; Chaidir, Taufik; Suprapti, Ida Ayu Putri (Eastasouth Institute, 2024)
This study aimed to examine and analyze the influence of e-wallet usage on consumptive behavior in the community of Mataram City, with self-control as a moderator. The population consists of Mataram City residents who use e-wallets and belong to the Zillennial or Gen Z generation, aged between 17 and 27 years old. The convenience sampling technique was employed to conduct the sampling. This study employed a quantitative research approach, collecting data via a questionnaire including statements that reflect the indicators of each construct. As the research variables were second-order, the approach used was the Embedded Two Stage Approach, involving two stages of testing: the first stage included an outer model test through validity and reliability tests on repeated indicators, while the second stage included an outer model test, inner model test, and hypothesis testing. The findings of this investigation demonstrated that consumer behavior was substantially and positively influenced by the use of e-wallets, while self-control did not significantly modulate the relationship between the two. Therefore, a good self-control should be enhanced, not only for long-term needs but also for short-term matters as well.